AKSESIBILITAS PENDIDIKAN GRATIS BAGI MASYARAKAT MISKIN PADA SEKOLAH SWASTA ISLAMIC BOARDING SCHOOL DI ACEH - Muazzinah Muazzinah (Al-Ijtima`i: International Journal of Government and Social Science, 2022)
The high interest of the Acehnese people towards education at private Islamic Boarding School schools, namely the integrated dayah, provides space for discrimination between students who are able and those who cannot. The purpose of this study was to examine access to policy and budget for the poor in obtaining education at integrated dayahs in Aceh. The research method uses a descriptive qualitative approach with data collection techniques by interview and documentation. The results found are in the formal legal aspect, accessibility from the central government is obtained by the poor, namely the existence of BOS and PIP, while the regional government of Aceh province is scholarship assistance for orphans, orphans, orphans and orphans but not specifically for the poor, while the internal Dayah policy is integrated is to determine their own policies such as the foster parent program, maximizing business entities implementing zakat mal dayah. In terms of budget sources, it can be seen from the APBN, DIPA and integrated Dayah internal finance.